Anti-inflammatory drugs as potential antimicrobial agents: a review - Okpala, Onyedika Emmanuel; Rondevaldova, Johana; Kokoska, Ladislav (Frontiers in Pharmacology, 2025)
The association and causal role of infectious agents in chronic inflammatory diseases have major implications for public health, treatment, and prevention. Pharmacological treatment of combined infectious and inflammatory diseases requires the administration of multiple drugs, including antibiotics and anti-inflammatory drugs. However, this can cause adverse effects, and therefore, dual-action drugs need to be developed. Anti-inflammatory drugs that have already shown antimicrobial properties appear to be promising candidates. NSAIDs, namely aceclofenac, diclofenac, and ibuprofen, were tested in clinical trials with patients diagnosed with uncomplicated urinary tract infections (UTIs) and cellulitis. The administration of ibuprofen, a drug tested in the highest number of studies, resulted in symptom resolution in patients with UTIs. Additionally, ibuprofen caused a high survival rate in mice infected with Pseudomonas aeruginosa and demonstrated potent in vitro antibacterial effects against Bacillus cereus, Escherichia coli, and Staphylococcus aureus, including methicillin-resistant S. aureus (MRSA) (MIC 0.625–2.5 mg/L). For most anti-inflammatory drugs, only data showing their in vitro and in vivo antimicrobial effects are available. Among these, auranofin caused a high survival rate in mice infected with Enterococcus faecium, S. aureus, and Clostridioides difficile. It also produced a strong in vitro growth-inhibitory effect against Streptococcus agalactiae, S. pneumoniae, S. aureus, S. epidermidis, Bacillus subtilis, C. difficile, E. faecalis, E. faecium, and Mycobacterium tuberculosis (MIC 0.0015–5 mg/L). Similarly, aspirin caused a high survival rate in M. tuberculosis-infected mice and strong to moderate in vitro activity against E. coli, B. cereus, P. aeruginosa, Enterobacter aerogenes, Klebsiella pneumoniae and Salmonella choleraesuis (MIC 1.2–5 mg/L). Moreover, topical application of celecoxib resulted in a high reduction in MRSA burden in mice. However, it only caused moderate in vitro effects against S. epidermidis, S. aureus and Bacillus subitilis (MIC 16–64 mg/L). These data suggest that certain non-steroidal anti-inflammatory drugs (NSAIDs) are promising drug candidates for the development of dual-action drugs for the potential treatment of combined infectious and inflammatory diseases such as tuberculosis, musculoskeletal infections and UTIs. Nevertheless, future clinical trials must be conducted to ascertain the antibacterial effect of these NSAIDs before their practical use.